RESILIENSI BAHASA LAMPUNG DI KALANGAN GENERASI Z: PERAN STRATEGIS PROGRAM STUDI PENDIDIKAN BAHASA LAMPUNG” - Latifa Eka Pratiwi; Nur Oktafia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Local languages represent a vital cultural heritage currently facing significant challenges due to globalization and digital transformation. This study aims to analyze the resilience of the Lampung language among Generation Z by examining the strategic role of the Lampung Language Education Study Program as an institutional agent. This research employed a qualitative-descriptive approach using phenomenological methods. Data were collected through in-depth interviews, participatory observations, and document analysis, and processed using the interactive model of Miles, Huberman, and Saldaña (2019).The findings reveal that Lampung language resilience operates through three main dimensions: individual resilience, digital resilience, and institutional resilience. Generation Z demonstrates a strong ethnolinguistic identity but tends to express it through digital platforms rather than formal interaction. The Lampung Language Education Program plays a crucial role in building a sustainable linguistic ecosystem through curriculum innovation, creative digital activities, and community engagement.This study proposes a new conceptual framework called the Institutional Linguistic Resilience (ILR) Model, which integrates personal, technological, and institutional factors to explain the sustainability of regional languages.